Produtividade e nutrição do milho após diferentes formas de aplicação de pó de rocha e esterco (Research, Society and Development, 2021)
The aim of this study was to evaluate the efficiency of rock powder applied isolated or associated with egg-laying hen manure as a source of nutrients for maize crop; and to evaluate the effect of application form in the efficiency of this sources in improve crop yield. The experiment was composed by eight treatments, distributed in a randomized block design and in factorial design 4 (A) x 2 (B), with four replicates. In factor A, the different sources of nutrients were allocated: rock powder; rock powder + egg-laying hen manure; egg-laying hen manure; and control; applied on the soil surface or incorporated with harrow. The doses used were 2 and 10 Mg ha-1 of rock powder and manure, respectively. Were evaluated: foliar nitrogen (N) and phosphorus (P) contents; extraction of N and P; and maize yield components. There was no interaction between the factors tested. The use of egg-laying hen manure isolated or associated with rock powder resulted in higher foliar P content, higher P extraction and increase in maize yield components, except for the number of plants per linear meter and cobs per plant. The application form did not affect the maize yield components, but when applied on the surface it increased foliar P content and P extraction. Rock powder is efficient in promoting better maize yield only when associated with manure. The incorporation of rock powder does not increase its efficiency in providing nutrients to the plants.